On Bézout inequalities for non-homogeneous polynomial ideals. (September 2021) - Hashemi, Amir; Heintz, Joos; Pardo, Luis M.; Solernó, Pablo
Abstract: We introduce a "workable" notion of degree for non-homogeneous polynomial ideals and formulate and prove ideal theoretic Bézout inequalities for the sum of two ideals in terms of this notion of degree and the degree of generators.